2019
DOI: 10.21791/ijems.2019.1.62.
|View full text |Cite
|
Sign up to set email alerts
|

Combustors with Low Emission Levels for Aero Gas Turbine Engines

Abstract: The aircrafts are responsible for emitting several types of pollutants, especially the pollutants in the form of NOX, CO2, CO, UHC, SOX and Particulate Matter PM (smoke/soot). The impact of aviation emissions on the global is well known, where these emissions modify the chemical and microphysical properties of the atmosphere resulting in changes of earth’s climate system, which can ultimate in critical changes in our planet fragile ecosystem, also the pollutants produced by aircraft engines cause many health p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The last combustor zone is the exhaust-air mixing and cooling zone. It can be concluded that throughout the combustion process in the combustor, the fuel-air mixture created and burned is in a lean state, which has a lower combustion temperature as a consequence, which permits to reduce the emissivity of the these combustors [6]. The LPP combustors must be adequately shaped to form a stable recirculation zone.…”
Section: Stoichiometric Combustion Avoiding In the Combustorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The last combustor zone is the exhaust-air mixing and cooling zone. It can be concluded that throughout the combustion process in the combustor, the fuel-air mixture created and burned is in a lean state, which has a lower combustion temperature as a consequence, which permits to reduce the emissivity of the these combustors [6]. The LPP combustors must be adequately shaped to form a stable recirculation zone.…”
Section: Stoichiometric Combustion Avoiding In the Combustorsmentioning
confidence: 99%
“…Compared to the LPP combustion chamber, the TAPS combustion chamber is characterized by greater flame stabilization safety by using a pilot flame on the low load of the drive unit. In addition, the combustion chamber is characterized by very low emissions of nitrogen oxides (NO x ); the third generation of TAPS combustors has reduced around 75% of nitrogen oxide (NO x ) emissions planned in the CAEP/6 [6]. Figure 4 shows the work principle of the TAPS combustor.…”
Section: Stoichiometric Combustion Avoiding In the Combustorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the increasingly stringent regulations for pollutant emissions published by International Civil Aviation Organization (ICAO), high efficiency and low pollution combustion have become important design standards for aeroengine gas turbine combustors. 1 Among numerous low pollution solutions, aeroengine manufacturers prefer the lean combustion technology due to its superior capability in reducing pollutants especially for thermal NOx. 2 Oriented by the lean combustion concept, several innovative combustors were invented and explored, such as GEnx TAPS (Twin Annular Premixing Swirler combustors) combustor, 3 Rolls Royce LDI (Lean Direct Injection combustors) combustor, 4 JAXA low NOx combustor 5 and Beihang TeLESS (Technology of Low Emission of Stirred Swirl) combustor.…”
Section: Introductionmentioning
confidence: 99%